2018
DOI: 10.1371/journal.pbio.2005707
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nicotinamide adenine dinucleotide reduced (NADH) oxidation links the tricarboxylic acid (TCA) cycle with methionine metabolism and nuclear DNA methylation

Abstract: Mitochondrial function affects many aspects of cellular physiology, and, most recently, its role in epigenetics has been reported. Mechanistically, how mitochondrial function alters DNA methylation patterns in the nucleus remains ill defined. Using a cell culture model of induced mitochondrial DNA (mtDNA) depletion, in this study we show that progressive mitochondrial dysfunction leads to an early transcriptional and metabolic program centered on the metabolism of various amino acids, including those involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 46 publications
3
86
0
Order By: Relevance
“…However, studies have also shown or suggested that mitochondria can influence nuclear gene expression and might be involved in the epigenetic regulation of the nuclear genome [9,12,17,[28][29][30][31][32]. For instance, depleting mitochondria in cultured human kidney cells caused changes in nuclear DNA methylation, an important bearer of epigenetic information [33]. It is therefore conceivable that different mito-nuclear combinations might be under different epigenetic regulations and might entail the reported changes in life-history traits or disease [10,16,17,22,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have also shown or suggested that mitochondria can influence nuclear gene expression and might be involved in the epigenetic regulation of the nuclear genome [9,12,17,[28][29][30][31][32]. For instance, depleting mitochondria in cultured human kidney cells caused changes in nuclear DNA methylation, an important bearer of epigenetic information [33]. It is therefore conceivable that different mito-nuclear combinations might be under different epigenetic regulations and might entail the reported changes in life-history traits or disease [10,16,17,22,34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much interest has been dedicated to the investigation of the correlation between mitochondrial dysfunction and its possible influence on the nuclear epigenome [10]. Attention has been focused on the level of reduced nicotinamide adenine dinucleotide (NADH) in mitochondria, suggesting a possible connection with methionine metabolism and the regulation of nuclear DNA methylation [11].…”
Section: Doi: 101159/000490751mentioning
confidence: 99%
“…Mitochondrial function affects many areas of cell biology but its impact on epigenetics has just lately gained attention. A decade ago, changes in DNA methylation as a function of mitochondrial DNA (mtDNA) content were first reported (1), and only recently has mitochondrial dysfunction resulting from progressive mtDNA depletion or complex III mutations been shown to alter the histone methylation and acetylation landscapes (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these epigenetic and transcriptional effects could be reversed by modulating the tricarboxylic acid (TCA) cycle through genetic or pharmacological means (3,4). Activation of the methionine salvage pathway was involved in DNA methylation changes while mitochondrial-derived acetyl-CoA was found to influence the histone acetylation landscape (3,4). Other links between mitochondrial metabolism and the epigenome involving increased reactive oxygen species (ROS) or altered abundance of other TCA cycle metabolites such as α-ketoglutarate or 2-hydroxyglutarate have also been proposed (2,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation